Morphological Character and Clorophyl Content Index of Corn Infected with Dowry Disease on Land Applied With Slow Realease Fertilizer Based on Corn Cob Biochar - Rahim, Iradhatullah; Nurbaya, Nurbaya; Ilmi, Nur; Sukmawati, Sukmawati; Putera, Muh Ikbal; Suherman, Suherman; Yamin, Mayasari (Journal of Agriculture, 2024)
Downy mildew is a significant disease of corn plants caused by the pathogenic fungus Peronosclerospora maydis, with attack rates reaching 95%. The application of slow-release fertilizer based on corn cob biochar is expected to increase the resistance of corn plants. Similarly, Bacillus sp. and Pseudomonas sp. are known as antagonistic microorganisms. Bacteria can produce antibiotic compounds that hydrolyze fungal cell walls, siderophores, and other antibiotic properties that inhibit pathogen growth. This study aims to determine the morphological characteristics of downy mildew-infected corn on biochar-applied land. Treatments were arranged factorially in a Factorial Randomized Block Design repeated four times. The treatment was the application of slow-release fertilizer from biochar mixed with NPK fertilizer, namely control, slow-release fertilizer, slow-release fertilizer + cow urine, and slow-release fertilizer + cow urine + bacteria (Azobacter and Bacillus). The results showed that slow-release fertilizer gave the best growth to both normal and downy mildew-affected maize plants. The stomata of typical corn leaves were more open with regular vascular bundles, while those affected by downy mildew had more closed and irregular stomata. The chlorophyll content index in downy mildew-affected maize can also improve by applying biochar-based slow-release fertilizer.